2022
DOI: 10.1002/advs.202105346
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Chromium Coordinated Graphitic Carbon Nitride for Bioinspired Antibiofouling in Seawater

Abstract: Artificial nanozymes exerting enzyme functionality are recognized as promising alternatives of natural enzymes in biomimetic chemistry. Natural haloperoxidases that utilize hydrogen peroxide (H2O2) to catalytically convert halide into strong biocidal hypohalous acid hold great promise for thwarting biofouling, while their practical application remains highly questionable as instability of natural enzymes and inadequate H2O2. Herein a semiconducting nanozyme consisting of chromium single atoms coordinated on ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 53 publications
(59 reference statements)
1
30
0
Order By: Relevance
“…[4,5] These metalloproteins are thought to exert a critical role in the marine biosynthesis of many halogenated organic products and could thus serve as the chemical defense system of marine organisms to fight against biofouling in seawater. [6,7] Traditional antibiofouling strategies based on releasing toxic chemical substances into marine environments, especially heavy metal biocides, are becoming a problem due to the nonselective lethal toxicity. [8][9][10] The sticker evaluation and regulations have promoted researchers to find ecofriendly anti-biofouling solutions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] These metalloproteins are thought to exert a critical role in the marine biosynthesis of many halogenated organic products and could thus serve as the chemical defense system of marine organisms to fight against biofouling in seawater. [6,7] Traditional antibiofouling strategies based on releasing toxic chemical substances into marine environments, especially heavy metal biocides, are becoming a problem due to the nonselective lethal toxicity. [8][9][10] The sticker evaluation and regulations have promoted researchers to find ecofriendly anti-biofouling solutions.…”
mentioning
confidence: 99%
“…However, the relatively low catalytic activity and inferior kinetics compared to natural enzymes restricted their applications. [6] In recent years, external stimuli represented a new mode of activity regulation of nanomaterials in biomimetic chemistry. For example, photo-antimicrobials, including…”
mentioning
confidence: 99%
“…Apart from GP and CNTs, the AF potential of other carbon nanomaterials has been explored. Recently, Luo et al synthesized atomic chromium–graphitic carbon nitride coatings and demonstrated their in situ activity to control marine biofouling for approximately 2 months [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nanozymes, known as nanomaterials possessing enzyme-like functionalities, have been widely applied in biological systems because of their benign biocompatibility, chemical stability, tunable activity, and scalable manufacture capability. Recently, exciting paradigms can be found for haloperoxidase-mimicking nanozymes, such as CeO 2 , V 2 O 5 , and tungsten engineering of metal–organic frameworks. However, even though some impressive preliminary results have been achieved, very few nanozymes with intrinsic haloperoxidase-like activity have been developed so far. Layered transition metal dichalcogenides have demonstrated superior performance in many fields, such as solid lubricants, energy devices, petrochemical catalysis, and so forth, due to their physicochemical diversity, low cost, and chemical stability. In view of these advantages, MoS 2 has been explored as a valuable nanozyme that exhibits multiple enzyme-mimicking activities, such as superoxide dismutases, catalases, and peroxidases, in combating oxidative stress and disinfecting drug-resistant bacteria. , Unfortunately, MoS 2 exhibited very poor haloperoxidase-mimicking activity, as experimentally revealed in this work.…”
Section: Introductionmentioning
confidence: 99%